Aspectos biológicos, ecológicos e genéticos da Melipona (Michmelia) capixaba - Moure e Camargo, 1994 (Hymenoptera, Apidae) - Nascimento, Vania Alves (1996)
The greatest diversity of Meliponinae is found in the Neotropical region, where more than 300 species have been described. In Brazil, these bees are the main pollinators of native flora. Melipona (Michmeliá) capixaba is endemic to the highland region of Espírito Santo. An attempt was made to increase the number of colonies of M. capixaba in the region of Domingos Martins (ES) by teaching division methods to the residents. To fulfill this goal 53 colonies were formed. The creation of Melipona capixaba in rational beehives was possible, and that the period from September 15 to March 30 is conducive to the division of colonies. The following natural enemies were identified: phorids (Pseudohypocera kerteszí), thief bees (Lestrimelitta lemon), spiders (Nephilengys cruentatá), ants, lizards, mammals such as cuíca (Marmosops sp) and irara (Eira barbará). The region of occurrence of M. capixaba is located between 700 and 1000 meters of altitude, has ombrófilo climate and formation type montana. The number of estimated sexual alleles for the population of M. capixaba in Domingos Martins was 24 and to maintain this number requires about one thousand colonies. To house this number of colonies, 28.26 km2 of forest is needed. The remaining Atlantic Forest fragments average 12.56 km2, separated by 2 to 11 km of fields or crops. By analysis of the polyacrylamide gel esterase profile it was found that hybridization occurred between M. capixaba and M. scutellaris.